Correlation of the oral microbiota with the periodontal health: a literature review - Calle Rodríguez , Ariana Pamela (2025)
The oral microbiota represents a dynamic and complex ecosystem that harbors between 500 and 1500 species of microorganisms, ranking second in diversity within the human organism. This literature review analyzes the relationship between the oral microbiota and periodontal health, examining the factors that influence its balance and the consequences of its disruption. The oral microbiota maintains a symbiotic balance, which is essential for oral health. The imbalance of this ecosystem (dysbiosis) is directly related to periodontal diseases, where Socransky's red complex, particularly the species Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia, play a fundamental role. Other relevant microorganisms such as Candida albicans, Enterococcus faecalis, Staphylococcus aureus, and Aggregatibacter actinomycetemcomitans are also identified. The composition of the oral microbiota can be affected by multiple variables, including ethnicity, genetics, geographic location, age, medication use, socioeconomic status, diet, human habitat, culture, and education. Within the oral cavity, a significant number of microorganisms are hosted, which actively participate in processes such as digestion and defense against pathogens. Additionally, this text explores the concepts of biofilm formation, bacterial equilibrium, and the mechanisms of bacterial action in the oral environment. Recommended probiotics for maintaining a balanced flora are discussed, along with host-related, environmental, pharmacological, and local factors that may disrupt the oral microbiota. Finally, the evolution of the oral microbiota is analyzed in relation to different stages of life, from the prenatal period to older adulthood.